A picture corrects a thousand words: the effect of photos on veracity feedback - Pulm, Claudine; Gast, Anne; Rummel, Jan (Consciousness and cognition, 2024)
The truthiness effect (Newman et al., 2012) refers to the belief that any particular stimulus is truthful when it is accompanied by nonprobative information (e.g., a photograph). Accordingly, photo-accompanied statements are more likely to be judged as truthful compared to statements without a photo. In an online experiment (N = 98) with two assessment times, we aimed to replicate this effect and its persistence over time. Furthermore, we were interested in to what extent feedback on the actual veracity of statements would be affected by the presence of a photo. Participants rated the veracity of trivia statements either accompanied by a nonprobative photo or not. Feedback on veracity, with or without a nonprobative photo, was provided after some but not all veracity judgments. The truthiness effect could neither be replicated immediately nor after 48 h. Feedback facilitated discrimination between true and false statements − especially when accompanied by a photo. However, feedback also led to a bias towards responding “true”. Our findings suggest using photos in feedback on veracity.
Gesehen am 05.03.2025